A 20-year retrospective clinical analysis of Candida infections in tertiary centre: Single-center experience. Issue 1 (January 2022) - Muzaheed,; Alshehri, Bashayer A.; Rabaan, Ali A.; El-Masry, Omar S.; Acharya, Sadananda; Alzahrani, Faisal M.; Al Mutair, Abbas; Alhumaid, Saad; Al-Tawfiq, Jaffar A.; Muhammad, Javed; Khan, Amjad; Dhama, Kuldeep; et al.
Abstract: Introduction: Fungal infections have risen exponentially in the last decade. In fact, candidiasis has become the most frequent type of hospital acquired infection especially in patients receiving treatment for chronic and terminal illnesses in a hospital. A retrospective analysis for a period of twenty year was undertaken to analyze the incidence rate of candidiasis, especially of Candida species, patients treated in a tertiary care center. Materials and methods: Clinical data was collected from samples of patients who were receiving tertiary care were presenting with clinically suspected fungal infections. Direct microscopy with 10% potassium hydroxide was done to visualize the presence of fungal elements, and Gram staining was done for any suspected yeast infection. The samples were inoculated on Sabouraud's Dextrose Agar and kept at 22 °C. Results: A total of 1256 samples with presumed fungal etiology were included in the study. The maximum number of fungal infections were present in elderly (70–79 years age). Females (53.8%) were more affected (45.5%). 21% isolates were identified as yeast but belonged to non- Candida fungi. Among Candida species, Candida albicans was the most dominant species (58.3%) followed by Candida glabrata (6.4%). The year-round data of fungal cases showed that the highest incident of Candida albicans infection were in January with a mean value of 3.80, while the lowest infections were reported in June, with prevalence of 2.32 of C. albicans . The twenty-year data analysis showed that the years 2001 and 2000 showed the highest incidents of C. albicans, with a mean prevalence of 7.50 and 6.83, respectively. Specimen vs fungal prevalence data showed that 38% of the C. albicans were isolated from body aspirate specimens, followed by 26% from swab specimens. Conclusion: The high prevalence of Candida spp. in the present study suggests increased susceptibility of patients with critical or chronic illnesses to fungal infections.